Unveiling the antiurolithiatic potentiality of two benzene sulfonamide derivatives against ethylene glycol-induced renal calculi - Ahmed M. Elgendy; Mohamed S. Nafie; Zohour I. Nabil; Nahla S. El-Shenawy; Heba N. Gad El-Hak (Nefrología)
Objective: Oxidative stress and inflammation play crucial roles in the onset of kidney injury and crystal formation caused by hyperoxaluria. Indapamide is a potent medication for treating renal calculi, but it has severe side effects such as hypokalemia, hypercalcemia, and hyperuricemia. Therefore, it is advisable to explore alternative treatments that do not have these side effects. The study aimed to reveal the antiurolithiatic potential of two benzene sulfonamide derivatives (SBCl and SBF; A and B, respectively) against ethylene glycol-induced kidney stones. Methods: The rats were divided into two main groups: the first group consisted of 20 rats with induced kidney stones, and the second group included 15 control rats. This division enabled a comparative analysis between rats with kidney stones and those without, offering insights into the effects of kidney stone induction on various physiological parameters and biochemical markers. The effectiveness of benzene sulfonamide derivatives (compounds A and B) was assessed in rats with induced kidney stones. The treatment was given orally by gavage for 21 days, administered every 48 h after inducing kidney stones with 0.12 ml of 5% ethylene glycol (EG). Results: The influence of compounds A and B on electrolytes, biochemical, antioxidant, and inflammatory reactions in induced kidneys underscores their potential therapeutic advantages in alleviating the advancement of kidney stone disease and related complications. Conclusion: Both compounds were found to possess equal effectiveness in inhibiting the complications of stone formation. However, SBCl-EG showed superior antioxidant and inflammatory parameters effects compared to SBF-EG. Our study's findings underscore the potential benefits of derivatives in treating nephrolithiasis and related oxidative disorders, highlighting their superior effects on antioxidant and inflammatory responses compared to standard treatments. Resumen: Objetivo: El estrés oxidativo y la inflamación juegan un papel esencial en la aparición de lesiones renales y la formación de cristales causadas por hiperoxaluria. Indapamida es una medicación potente para tratar los cálculos renales, pero tiene efectos secundarios graves tales como hipocalemia, hipercalcemia e hiperuricemia. Por tanto, es aconsejable explorar tratamientos alternativos que no tienen dichos efectos secundarios. El objetivo de este estudio fue revelar el potencial antiurolitiásico de dos derivados de sulfinamida de benceno (SBCl y SBF; A y B, respectivamente) para combatir los cálculos renales inducidos por etilenglicol. Métodos: Se dividió a las ratas en dos grupos principales: el primero de ellos incluyó 20 ratas con cálculos renales inducidos, incluyendo el segundo 15 ratas de control. Dicha división permitió realizar un análisis comparativo entre las ratas con cálculos renales y las que carecían de ellos, proporcionando información sobre los efectos de la inducción de cálculos en diversos parámetros fisiológicos y marcadores bioquímicos. Se evaluó la efectividad de los derivados de sulfinamida de benceno (compuestos A y B) en ratas con cálculos renales inducidos. El tratamiento fue administrado oralmente mediante sonda durante 21 días, cada 48 h, tras la inducción de cálculos renales con 0,12 ml de 5% etilenglicol (EG). Resultados: La influencia de los compuestos A y B en las reacciones electrolíticas, bioquímicas, antioxidantes e inflamatorias en los riñones inducidos destaca sus ventajas terapéuticas potenciales en cuanto a la mitigación del avance de los cálculos renales y sus complicaciones relacionadas. Conclusión: Se encontró que ambos compuestos poseen igual efectividad a la hora de inhibir las complicaciones de la formación de cálculos. Sin embargo, SBCl-EG reflejó efectos superiores de los parámetros antioxidantes e inflamatorios en comparación con SBF-EG. Los hallazgos de nuestro estudio destacan los beneficios potenciales de los derivados a la hora de tratar la nefrolitiasis y los trastornos oxidativos relacionados, subrayando sus efectos superiores en las respuestas antioxidante e inflamatoria, en comparación con los tratamientos estándar.